Knowledge, perceptions and practices associated with timing for breast cancer screening among female students at the University of Zimbabwe: A cross-sectional study - Peter Chikuvadze; Grace Nkhoma; Maxwell Mhlanga; Augustine Ndaimani (NSC Nursing)
Background: Breast cancer remains one of the leading causes of cancer-related mortality among women globally. Early detection through screening is crucial for improving outcomes. However, knowledge gaps, misconceptions, and poor practices around screening timing persist among young women. This study explores the knowledge, perceptions, and practices related to breast cancer screening among female students at the University of Zimbabwe. It aims to inform nursing practice by highlighting the critical role nurses play in addressing these gaps through education, awareness, and guidance on screening timing. Methods: This analytical cross-sectional study employed random sampling to recruit participants at the University of Zimbabwe from March 4 to April 8. A structured questionnaire with three sections, consisting of closed-ended questions, was used to assess demographic characteristics, as well as knowledge, perceptions, and practices related to breast cancer screening. Data were analyzed using STATA 15, with descriptive statistics presented in tables and figures. Associations between variables were tested using Chi-square, Fisher’s exact tests, and binary logistic regression. Results: Of the 139 participants, 85% were aged 20-25, single, and undergraduates. Among all age groups, 54% did not perform breast self-examinations. Participants aged 36-40 had significantly higher odds of late screening (OR=17.8, p=0.014) and married participants also had higher odds of later screening (OR=4.42, p=0.009) compared to single participants. Participants who perceived that a healthy diet reduces breast cancer risk had lower odds of late screening (OR=0.32, p=0.021). Participants who knew the recommended age of Breast Self-Examination had higher odds of late screening (OR=2.5, p=0.027). Participants with religious and cultural beliefs influencing their decision-making were significantly more likely to present late (OR = 3.21, p = 0.030). Conclusion: Socio-demographic factors and health-seeking behaviors significantly influenced breast cancer screening timing. Nurses are pivotal in promoting early screening through tailored health promotion strategies, including raising awareness, addressing misconceptions, and encouraging self-examination practices.